Did the CDS Market Push up Risk Premia for Sovereign Credit? - Sergio Andenmatten; Felix Brill (Swiss Journal of Economics and Statistics, 2011)
We examine the empirical relationship between credit default swap (CDS) premia and government bond spreads for Portugal, Italy, Ireland, Greece, and Spain (the 'PIIGS' countries). We find some evidence for a long-run relationship in the sense of cointegration for the two markets. In most cases (five out of seven), only CDS premia contribute to the price discovery process. In the other cases, both markets make a more or less equal contribution. All in all, this suggests that bond spreads react only sluggishly to long-term imbalances, as measured by the cointegrating relationship. In light of this, we can conclude that, in most cases, CDS markets are leading markets if there is a long-run relationship between the CDS and gov-ernment bond spread markets. This may partly be due to liquidity effects.
Keywords: C58; G01; G12; G15; 330; Greek debt crisis; sovereign credit; CDS market; price discovery